Macroeconomic impacts of foreign exchange reserve accumulation: Theory and international evidence - Shin-ichi Fukuda; Yoshifumi Kon (Asian Development Bank Institute (ADBI), 2010)
Recently, a dramatic accumulation in foreign exchange reserves has been widely observed in developing countries. This paper explores the possible long-run impacts of this trend on macroeconomic variables in developing countries. We analyze a simple open economy model where increased foreign exchange reserves reduce the costs of liquidity risk. Given the amount of foreign exchange reserves, utility-maximizing representative agents decide consumption, capital stock, and labor input, as well as the amounts of liquid and illiquid external debt. The equilibrium values of these variables depend on the amount of foreign exchange reserves. A rise in foreign exchange reserves increases both liquid and total debt, while shortening debt maturity. To the extent that interest rates of foreign exchange reserves are low, an increase in foreign reserves also leads to a permanent decline in consumption. However, when the tradable sector is capital intensive, the increase may enhance investment and economic growth. We provide empirical support for our theoretical analysis using panel data from the Penn World Table. The cross-country evidence shows that an increase in foreign exchange reserves raises external debt outstanding and shortens debt maturity. The results also imply that increased foreign exchange reserves may lead to a decline in consumption, but can also enhance investment and economic growth. The positive impact on economic growth, however, disappears when we control the impact through investment.
Keywords: F21; F32; F34; 330; Währungsreserven; Makroökonomischer Einfluss; Gesamtwirtschaftliche Liquidität; Offene Volkswirtschaft; Schätzung; Entwicklungsländer; Welt